Management of banana pseudostem weevil odoiporus longicollis oliv.using entomopathogenic fungi - Sahi Beegum M K (Department of Agricultural Entomology, College of Agriculture, 2005)
Investigation on “Management of banana pseudostem weevil, Odoiporus longicollis Oliv. using entomopathogenic fungi” was carried out in the Department of Agricultural Entomology, College of Agriculture, Vellayani. The study was conducted to screen four entomopathogenic fungi, to evaluate their biocontrol potential and to standardize the effective dose and method of application for the management of the banana pseudostem weevil. Four entomopathogenic fungi viz., Metarhizium anisopliae, Beauveria bassiana, Paecilomyces lilacinus and Nomuraea rileyi were tested against O. longicollis. Among them M. anisopliae and B. bassiana were found to infect O. longicollis grubs. Susceptibility of different stages of grubs to fungal infection was tested by using first, second, third, fourth and fifth instar grubs of O. longicollis and the results revealed that first and second instar grubs were more susceptible to fungal infection. Determination of effective dose of fungi against second instar grubs of O. longicollis was carried out by spraying the grubs with different concentrations of M. anisopliae and B. bassiana. The LC50 values of M. anisopliae and B. bassiana were 3.9 x 106 spores ml-1 and 1.6 x 105 spores ml-1 respectively. Evaluation of six naturally available solid media viz., rice bran, wheat bran, guinea grass, gingelly oil cake, coir pith, and neem cake were carried out for mass multiplication of M. anisopliae and B. bassiana. The results revealed that both rice bran and wheat bran were suitable for the mass multiplication of these fungi. The spore production was 9.26 x 106 spores ml-1 and 8.71 x 106 spores ml-1 respectively for M. anisopliae on first week after inoculation. For B. bassiana, the spore count was 503.42 x 106 spores ml-1 and 320.32 x 106 spores ml-1 respectively on first week after inoculation. Among the liquid media tried, coconut water and rice bran extract produced maximum mycelial growth and sporulation of fungi. For M. anisopliae the spore count was 7.77 x 107 spores ml-1 and 0.49 x 107 spores ml-1 respectively. B. bassiana recorded 440.03 x 106 spores ml-1 and 232.26 x 106 spores ml-1 respectively. M. anisopliae and B. bassiana grown in rice bran and wheat bran recorded maximum virulence on two weeks after storage and decreased thereafter. However, coconut water and rice bran extract showed maximum virulence on first week after storage and then found decreasing. Studies conducted to evaluate the compatibility of fungi with NeemAzal 0.4 per cent, chlorpyriphos 0.03 per cent, copper oxychloride 0.4 per cent and mancozeb 0.3 per cent revealed that all the pesticides tested inhibited the growth of M. anisopliae and B. bassiana. But the per cent inhibition was least in the case of NeemAzal 0.4 per cent. Field experiments were conducted with M. anisopliae and B. bassiana with chlorpyriphos (0.03 per cent) and NeemAzal (0.4 per cent) as checks. The plants were artificially infested with known number of grubs. Two experiments were conducted, one with prophylactic treatments and the other with curative treatments. Three application methods viz., leaf axil filling of spore suspension of M. anisopliae and B. bassiana, leaf axil filling of fungi in rice bran and stem injection of spore suspension were tested. Among these treatments leaf axil filling of B. bassiana spore suspension at 1.8 x 107 ml-1 as prophylactic treatment was most effective which gave 52.42 per cent mortality of grubs.